The Habitats Humans Provide: Factors affecting the diversity and composition of arthropods in houses. Issue 1 (December 2017) - Leong, Misha; Bertone, Matthew; Savage, Amy; Bayless, Keith; Dunn, Robert; Trautwein, Michelle
Abstract The indoor biome is a novel habitat which recent studies have shown exhibit not only high microbial diversity, but also high arthropod diversity. Here, we analyze findings from a survey of 50 houses (southeastern USA) within the context of additional survey data concerning house and room features, along with resident behavior, to explore how arthropod diversity and community composition are influenced by physical aspects of rooms and their usage, as well as the lifestyles of human residents. We found that indoor arthropod diversity is strongly influenced by access to the outdoors and carpeted rooms hosted more types of arthropods than non-carpeted rooms. Arthropod communities were similar across most room types, but basements exhibited more unique community compositions. Resident behavior such as house tidiness, pesticide usage, and pet ownership showed no significant influence on arthropod community composition. Arthropod communities across all rooms in houses exhibit trophic structure—with both generalized predators and scavengers included in the most frequently found groups. These findings suggest that indoor arthropods serve as a connection to the outdoors, and that there is still much yet to be discovered about their impact on indoor health and the unique ecological dynamics within our homes.